A scaffolding framework using mind maps and metacomponents to improve real-world physics problem-solving skills - Siti Nazirah Butai; Fatin Aliah Phang (Bitara, 2024)
Traditionally, physics problem-solving has mainly focused on mathematical procedures and quantitative analysis, often leading students to rely on memorization and repetitive drills. However, introduction to real-world physics problem-solving (RWPPS) has proven to provide students with skills that can be applied in various real-world situations beyond the classroom. RWPPS is considered a complex problem-solving process with a combination of multiple skills, making it challenging for students. Metacomponents are higher-order control processes that are used for planning how a problem should be solved, deciding on which strategy should be used during problem-solving and monitoring the success of one’s problem-solving. Therefore, this paper synthesizes literature in RWPPS and metacomponents to develop a conceptual framework to implement a suitable scaffolding strategy for pre-university students to improve their RWPPS skills. Vygotsky's theory of Social Constructivism, which is based on the concept of Zone of Proximal Development (ZPD), is used as a basis for evaluating the development of students' skills in RWPPS. This framework incorporates mind maps as a scaffolding tool and metacomponents as an executive process to assist students in planning, monitoring, and evaluating their problem-solving process. Through this proposed framework, it is hoped that students will be able to surpass their ZPD, providing a more structured teaching approach to solving real-world physics problems and enhancing their skills to meet the challenges of the 21-st century.